PENERAPAN MODEL PEMBELAJARAN TACTICAL GAME TERHADAP KEMAMPUAN LAY UP SHOOT BOLA BASKET - Bobi, Bobi; Simanjuntak, Victor G; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe problem in this research is, there are still many students who do not understand how to do basic lay-up shoot techniques and are still wrong in doing so. This study aims to determine the effect of the tactical game learning model on the ability to shoot up shoot students of SMPN 1 Sungai Raya. This research uses a descriptive method. The form of research used is classroom action research (CAR). In this classroom action research, the actions that are carried out are ongoing and the actions will be carried out in cycles given to the students the researcher makes as research subjects. The subjects of this study were students of class VII D of SMP Negeri 1 Sungai Raya in 2018/2019 school year, totaling 20 students. Results of the analysis In the first cycle there were 13 students who completed or totaled 65% while those who did not complete 7 students or 35% then proceeded to the second cycle with all categories complete with 20 students or 100% including in the complete category. From these results it shows that the basic lay up shoot technique research through the application of tactical game learning has been successfully carried out because it is more than KKM which is 75%. Thus it can be concluded that the learning of lay lay shoot basic techniques through the application of the tactical game learning model has a positive impact on students while learning the basic lay-up shoot techniques in basketball games and provides a significant increase in lay-shoot shoot learning outcomes.Â Keywords: Learning Tactical Game, Lay Up Shoot, Basketball